Biochemistry‐Guided Prediction of the Absolute Configuration of Fungal Reduced Polyketides. (14th September 2021) - Takino, Junya; Kotani, Akari; Ozaki, Taro; Peng, Wenquan; Yu, Jie; Guo, Yian; Mochizuki, Susumu; Akimitsu, Kazuya; Hashimoto, Masaru; Ye, Tao; Minami, Atsushi; Oikawa, Hideaki
Abstract: Highly reducing polyketide synthases (HR‐PKSs) produce structurally diverse polyketides (PKs). The PK diversity is constructed by a variety of factors, including the β‐keto processing, chain length, methylation pattern, and relative and absolute configurations of the substituents. We examined the stereochemical course of the PK processing for the synthesis of polyhydroxy PKs such as phialotides, phomenoic acid, and ACR‐toxin. Heterologous expression of a HR‐PKS gene, a trans‐acting enoylreductase gene, and a truncated non‐ribosomal peptide synthetase gene resulted in the formation of a linear PK with multiple stereogenic centers. The absolute configurations of the stereogenic centers were determined by chemical degradation followed by comparison of the degradation products with synthetic standards. A stereochemical rule was proposed to explain the absolute configurations of other reduced PKs and highlights an error in the absolute configurations of a reported structure. The present work demonstrates that focused functional analysis of functionally related HR‐PKSs leads to a better understanding of the stereochemical course. Abstract : We performed a focused analysis of functionally related polyketide synthases (PKSs) which produce linear polyketides (PKs) such as prophialotide and other polyhydroxy PKs. The relative and absolute configurations were determined by degradation studies. Based on the results, we propose a stereochemical rule during the chain‐elongation process of the reduced PKs.